2019
DOI: 10.1097/brs.0000000000003068
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural Adaptation and Validation of the Hausa Version of the Oswestry Disability Index 2.1a for Patients With Low Back Pain

Abstract: Study Design. Validation of a translated, culturally adapted questionnaire. Objective. To translate the Oswestry Disability Index (ODI) version 2.1a into Hausa Language and to validate its use in a cohort of patients with low back pain (LBP). Summary of Background Data. The ODI is one of the most commonly used condition-specific questionnaires for assessing functional disability in patients with LBP, yet, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 54 publications
4
36
1
1
Order By: Relevance
“…It was not too low (i.e., lack of association between the items), nor too high (i.e., redundancy of some items) [40]. In comparison with previous reports, the internal consistency value of the Arabic-MODQ is higher than the value of the Persian-MODQ [38] (see Table 6), and comparable with the values of some validation studies of the ODQ (0.83-0.87) [13,17,19,20,[23][24][25]55,57,59].…”
Section: Plos Onesupporting
confidence: 82%
See 2 more Smart Citations
“…It was not too low (i.e., lack of association between the items), nor too high (i.e., redundancy of some items) [40]. In comparison with previous reports, the internal consistency value of the Arabic-MODQ is higher than the value of the Persian-MODQ [38] (see Table 6), and comparable with the values of some validation studies of the ODQ (0.83-0.87) [13,17,19,20,[23][24][25]55,57,59].…”
Section: Plos Onesupporting
confidence: 82%
“…Floor and/or ceiling effects exist if more than 15% of respondents obtained the maximum or minimum possible score [40]. Floor and ceiling effects were defined by computing the number of respondents who scored the lowest status (90-100) or the highest status (0-10), respectively, on the Arabic-MODQ [13].…”
Section: Data Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher internal consistency > 0.95 would have indicated a redundancy in the questionnaire items. The internal consistencies of most of the ODI translations [37, 39, 40] fall within this band.…”
Section: Discussionmentioning
confidence: 92%
“…The two-factor model in this study differs from the two-factor models reported by previous studies on the ODI. Such factors reported include social/ recreational activities and non-recreational activities [37], dynamic and static activities [46, 49], pain-related activity, and pain intensity and pain-related participation [39]. Further, the item loadings of the various two-factor models are dissimilar.…”
Section: Discussionmentioning
confidence: 99%